Advancing food preservation with quercetin-based Nanocomposites: Antimicrobial, antioxidant, and controlled-release strategies - A review - Sakshi Jasrotia; Sonali Gupta; Manas Laxman Kudipady; Yashoda Malgar Puttaiahgowda (Current Research in Food Science)
The global food waste crisis, driven by rapid spoilage and oxidative degradation, substantiates the urgent need for sustainable packaging innovations. Though mechanically robust, conventional petroleum-based polymers contribute significantly to environmental pollution due to their non-biodegradability. Quercetin (Qr), a bioactive flavonoid with potent antimicrobial and antioxidant properties, has emerged as a promising component in next-generation active packaging. This review examines Qr-functionalized nanocomposite films, focusing on their ability to inhibit pathogens (e.g., Escherichia coli, Salmonella, Staphylococcus aureus) and prevent oxidative damage through radical scavenging and metal chelation. Advanced fabrication methods like solution casting and electrospinning enhance Qr's controlled release, mechanical strength, and UV-shielding capabilities. The synergistic use of biopolymers (e.g., CS, PVA) and nanofillers (e.g., ZnO, Ag NPs) further enhances thermal stability, biodegradability, and antimicrobial performance. Studies show that Qr-based films can extend food shelf life by up to 50 %, significantly reducing microbial loads and oxidative markers. Despite its GRAS status, challenges like production scalability, cost-effectiveness, and long-term stability remain. By integrating nanotechnology with bioactive compounds like Qr, this innovation represents a paradigm shift toward intelligent, eco-friendly packaging aligned with the United Nations Sustainable Development Goals (SDGs).